2021
DOI: 10.4103/jhrs.jhrs_14_21
|View full text |Cite
|
Sign up to set email alerts
|

The effect of endometrial polyp resection by office hysteroscopy during in vitro fertilization/intracytoplasmic sperm injection treatment cycle on pregnancy rate a series of 25 cases

Abstract: Aim: This study aims to evaluate the effect of endometrial polyp resection by office hysteroscopy during in vitro fertilisation/intracytoplasmic sperm injection (IVF/ICSI) treatment cycle on pregnancy rate. Setting and Design: A retrospective observational study (case series). Materials and Methods: Twenty-five patients from a total of 346 patients that started IVF/ICSI treatment due to different causes of infertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…). Likewise, Al-Rshoud et al demonstrated that out of the total of 49 patients diagnosed with PCOS, 15 patients (31%) were con rmed to possess uterine anomalies(17). As well, Saleh et al's study showed that uterine abnormalities were present in nearly one-third (n = 149, 31.4%) of the 409 patients with diagnosed PCOS(p < 0/001) (18).…”
mentioning
confidence: 95%
“…). Likewise, Al-Rshoud et al demonstrated that out of the total of 49 patients diagnosed with PCOS, 15 patients (31%) were con rmed to possess uterine anomalies(17). As well, Saleh et al's study showed that uterine abnormalities were present in nearly one-third (n = 149, 31.4%) of the 409 patients with diagnosed PCOS(p < 0/001) (18).…”
mentioning
confidence: 95%